Measles: To Vaccinate or Not?. Issue 4 (July 2015) - Beal, Judy A.
Abstract : A recent measles outbreak has highlighted the importance of vaccination for all eligible children. Our pediatric nursing expert suggests resources so you can be up-to-date on the latest information to share with parents.